1999
DOI: 10.1348/096317999166527
|View full text |Cite
|
Sign up to set email alerts
|

Expectancy‐value theory and predicting future employment status in the young unemployed

Abstract: A notable feature of research designed to investigate the predictors of future employment status is the absence of any theoretical framework. The ability of expectancy-value theory to predict future employment status was evaluated by interviewing 200 young unemployed people and measuring their employment status (unemployed, temporarily or permanently employed) 10-12 months later. Job expectancy and job importance predicted future employment status, separated the three groups of employment status at follow-up, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 10 publications
2
18
0
1
Order By: Relevance
“…Specifically, both relate to one's capacity to successfully accomplish specific future tasks. Self-efficacy (Judge & Bono, 2001;Stajkovic & Luthans, 1998) and outcome expectancy (Feather, 1992;Lynd-Stevenson, 1999) have predicted job performance and goal achievement respectively. Relatedly, the performance and leadership research domain has empirically shown that performance depends upon employees' possessing appropriate skills and competencies (e.g., Campbell, McCloy, Oppler, & Sager, 1993).…”
Section: Job Performance and Basic Psychological Need Satisfactionmentioning
confidence: 99%
“…Specifically, both relate to one's capacity to successfully accomplish specific future tasks. Self-efficacy (Judge & Bono, 2001;Stajkovic & Luthans, 1998) and outcome expectancy (Feather, 1992;Lynd-Stevenson, 1999) have predicted job performance and goal achievement respectively. Relatedly, the performance and leadership research domain has empirically shown that performance depends upon employees' possessing appropriate skills and competencies (e.g., Campbell, McCloy, Oppler, & Sager, 1993).…”
Section: Job Performance and Basic Psychological Need Satisfactionmentioning
confidence: 99%
“…This is a behavioral version of the rational choice model in economic decision making; it states that behavior is determined by conscious choice [38]. According to Lynd-Stevenson [26], EVT is a cognitive-motivational theory that relates an individual's level of motivation to the expectations and value/valence (positive or negative) held by the individual on reaching a goal. Research with EVT can be found in the fields of social and applied psychology; e.g., in evaluating the relative strength of intrinsic versus extrinsic valences in the motivational process [31] and for exploring the behavior of individuals alone or in a group setting [8]-key requirements for investigating the motivations of OSS developers.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Feather & O'Brien, 1987;Lynd-Stevenson, 1999), assessed people's expectations about finding a job. Internal consistency of the scale was 0.75.…”
mentioning
confidence: 99%